CO2 capture behavior and chemical structure of the alkali zirconate-silicate hybrid sorbent from ZrSiO4 by alkali activation method. Issue 51 (September 2021) - Wang, Zirui; Liu, Weihua; Ling, Changjian; Xu, Qian; Tang, Zhongfeng
Highlights: Zirconate-silicate hybrids were prepared as high temperature CO2 capture sorbent. CO2 adsorption/desorption dynamics of hybrid were studied by the different methods. Si-OH groups diffuse into alkali and condensate to form SiOSi bonds in interphase. The electron-donating ability determines chemical structure and CO2 storage capacity. Abstract: The zirconate-silicate hybrid as CO2 capture sorbent at high temperature were decomposed from ZrSiO4 by NaOH and KOH. The chemical structure and CO2 adsorption/desorption dynamics of zirconate-silicate hybrid were studied by the Fourier transform infrared, X-ray photoelectron spectroscopy and the thermogravimetric measurements. The results show that alkali divides ZrSiO4 into ZrO2 and Si-OH groups, then Si-OH groups diffuse into molten alkali and condensate to form a silicate shell with CO2 capture capacity on the surface of alkali activation products. The electron-donating ability of the molten alkali determines the chemical structure and the CO2 storage capacity of sorbents. When the ratio of NaOH to ZrSiO4 is 6:1, the sorbent with the optimal chemical structure for CO2 capture can be acquired after the alkali activation reaction. The CO2 capture process is kinetically controlled by metal cation diffusion after the carbonate-oxide external shell is formed, and the diffusion process is more dependent on the chemical structure of silicates in the zirconate-silicate hybrid than CO2 direct chemisorption reaction.